The Full-Size ABCG Transporter of Medicago truncatula Is Involved in Strigolactone Secretion, Affecting Arbuscular Mycorrhiza - Banasiak, Joanna; Borghi, Lorenzo; Stec, Natalia; Martinoia, Enrico; Jasiński, Michał (Frontiers in Plant Science, 2020)
Strigolactones (SLs) are plant-derived signaling molecules that stimulate the hyphal branching of arbuscular mycorrhizal fungi (AMF), and consequently promote symbiotic interaction between the fungus and the plant. Currently, our knowledge on the molecular mechanism of SL transport is restricted to the Solanaceae family. In the Solanaceae family, SL translocation towards the rhizosphere occurs through the exodermis via hypodermal passage cells and involves a member of the G subfamily, of the ATP-binding cassette (ABC) membrane transporters. Most Fabaceae species, including those that are agriculturally important, have a different root anatomy compared to most angiosperm plants (i.e., lacking an exodermis). Thus, we have investigated how SL transport occurs in the model legume Medicago truncatula. Here, we show that overexpression of a SL transporter from petunia (PaPDR1) enhances AMF colonization rates in M. truncatula. This result demonstrates the importance of ABCG proteins for the translocation of orobanchol-type molecules to facilitate arbuscular mycorrhiza, regardless of root anatomy and phylogenetic relationships. Moreover, our research has led to the identification of Medicago ABCG59, a close homologue of Petunia PDR1, that exhibits root specific expression and is up-regulated by phosphate starvation as well as in the presence of rac-GR24, a synthetic SL. Its promoter is active in cortical cells, root tips, and the meristematic zone of nodules. The mtabcg59 loss-of-function mutant displayed a reduced level of mycorrhization compared to the WT plants but had no impact on the number of nodules after Sinorhizobium meliloti inoculation. The reduced mycorrhization indicates that less SLs are secreted by the mutant plants, which is in line with the observation that mtabcg59 exudates exhibit a reduced stimulatory effect on the germination of the parasitic plant Phelipanche ramosa compared to the corresponding wild type.